1983
DOI: 10.1002/phar.1983.3.2p2.9
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Animal and Clinical Pharmacology of Diflunisal

Abstract: Diflunisal is a new salicylic acid derivative identified after a search for a compound with improved potency, enhanced gastrointestinal tolerance relative to its antiinflammatory activity, and a longer duration of action than that of aspirin. Animal and clinical studies have confirmed these properties. As an inhibitor of cyclooxygenase tested in vitro in a sheep seminal vesicle preparation, diflunisal was less potent than indomethacin but 10 to 20 times more active than aspirin. In addition, it was shown bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Areas under the diflunisal plasma concentration-time curve have been shown to increase disproportionately with dose (Tocco et al, 1975;Davies, 1983). Subjects receiving repeated oral doses of diflunisal in the range of 250 to 1000 mg day-' showed a more than proportional increase in steady-state diflunisal plasma concentrations with dose rate, and terminal elimination half-life of diflunisal Urinary recovery of DAG measured by direct injection of dilute urine (E) or following alkaline hydrolysis (U).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas under the diflunisal plasma concentration-time curve have been shown to increase disproportionately with dose (Tocco et al, 1975;Davies, 1983). Subjects receiving repeated oral doses of diflunisal in the range of 250 to 1000 mg day-' showed a more than proportional increase in steady-state diflunisal plasma concentrations with dose rate, and terminal elimination half-life of diflunisal Urinary recovery of DAG measured by direct injection of dilute urine (E) or following alkaline hydrolysis (U).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports, including the original biotransformation study by Tocco et al (1975) indicate that the disposition kinetics of diflunisal in man are dose-dependent (Davies, 1983;Dresse et al, 1979;Meffin et al, 1983;Tempero et al, 1977;Verbeeck et al, 1979). The mechanism(s) responsible for the dose-dependent pharmacokinetics of diflunisal in man has (have) not been identified although saturation of one or more of the conjugation pathways may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the pharmacokinetics of diflunisal are concentrationdependent (Davies, 1983;Loewen et al, 1988;Meffin et al, 1983). Following administration of single doses, this concentration-dependency seemed to arise mainly from saturation of the formation of the acyl glucuronide (Loewen et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Blood for drug quantification was withdrawn at the following time intervals from an indwelling catheter (heparin flushed) in the left cubital vein; prior to and at 0.083,0.25,0*5,0.75, 1, 1-25, 1.5, 1-75,2, 2.5, 3, 33, 4,5,6,7,8,24, and 48 h after dosing. Urine was collected for 48 h in fractionated portions.…”
Section: Design Ofthe Studymentioning
confidence: 99%
“…diflunisal, were de~eloped.~ Diflunisal is more lipophilic and shows a retarded absorption as compared to aspirin. 4 Attempts to accelerate diflunisal absorption by modifying formulations have been proved so far to be unsuccessful. 5 In the course of testing galenic .alternatives in healthy volunteers, we observed that increased gastric pH enhanced the absorption rate of the The purpose of this study is to investigate the mechanism involved in the absorption of diflunisal by modifying the gastric pH by coadministration of sodium bicarbonate.…”
Section: Introductionmentioning
confidence: 99%